Enhancement in rate of photocatalysis upon catalyst recycling - Sorathiya, Kalpesh; Mishra, Biswajit; Kalarikkal, Abhishek; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Khushalani, Deepa (Scientific Reports, 2016)
Recyclability is an important aspect for heterogeneous photo-catalysts. Ease of recovery and stability of the photo-catalyst in terms of efficiency over the number of cycles are highly desired and in fact it is ideal if the efficiency is constant and it should not decrease marginally with each cycle. Presented here is a seminal observation in which the photocatalytic activity is shown to improve with increasing number of catalytic cycles (it is 1.7 times better after the 1st cycle and 3.1 times better after the 2nd cycle). Specifically, nanorods of pure TiO2 and TiO2 doped with controlled amount of tungsten have been used to degrade two model pollutants: Phenol and Rhodamine B under exclusive visible light illumination. It was found that, in case of 1 mol.% W incorporation, rate of photocatalysis and also the range of visible light absorption of the photocatalyst increased after the photocatalysis as compared to before photocatalysis. This aspect is unique for doped TiO2 and hence provides an intriguing way to mitigate low photoactivity.

Three way catalytic converter reactions aspects at near ambient temperatures on modified pd-surfaces - Roy, Kanak; Jain, Ruchi; Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Comptes Rendus Chimie, 2016)
The dissolution of oxygen in palladium plays an important role in palladium catalysis. The present study shows that the surface modification (SM) due to the dissolution of atomic oxygen into the subsurfaces of palladium can be used as a control to tune its catalytic activity. CO oxidation and NO + H-2 + O-2 reaction was separately carried out on metallic Pd and on surface modified Pd using a molecular beam instrument and the results were compared. The metallic Pd does not show activity below 400 K for both reactions, whereas the SM-Pd shows activity at near-ambient temperatures. The electronic change due to SM was investigated using ambient pressure photoelectron spectroscopy, and the investigation clearly shows the effect of subsurface oxygen in the ambient temperature activity of palladium. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.

Ambient CO oxidation on in-situ generated Co3O4 spinel surfaces with random morphology - Dubey, Anjani; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ChemistrySelect, 2017)
The influence of the Co3O4 morphology on its redox behavior and catalytic performance in the CO oxidation reaction is studied. Three different Co3O4 morphologies were synthesized by precipitation and hydrothermal methods. TEM and SEM observations clearly show the different obtained morphologies: rods, wires and a mixture of plates and cubes. The textural properties depend on the morphology and the redox ones on the particle size. XRD analysis reveals a spinel structure in all solids but a preferential exposition of the [110] plane is presented in the Co3O4 rods. This preferential exposition, along with its higher specific surface area provides the rods with more efficient oxygen storage capacity resulting in an excellent catalytic performance compared to the other two morphologies.

Copper Cobalt Sulfide Nanosheets Realizing a Promising Electrocatalytic Oxygen Evolution Reaction - Chauhan, Meenakshi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Catalysis, 2017)
Nanostructured CuCo2S4, a mixed metal thiospinel, is found to be a benchmark electrocatalyst for oxygen evolution reaction (OER) in this study with a low overpotential, a low Tafel slope, a high durability, and a high turnover frequency (TOF) at lower mass loadings. Nanosheets of CuCo2S4 are realized from a hydrothermal synthesis method in which the average thickness of the sheets is found to be in the range of 815 nm. Aggregated nanosheets form a highly open hierarchical structure. When used as an electrocatalyst, CuCo2S4 nanosheets offer an overpotential value of 310 mV at a 10 mA cm(2) current density, which remains consistent for 10000 measured cycles in a 1 M KOH electrolyte. A chronoamperometric study reveals constant oxygen evolution for 12 h at a 10 mV s(-1) scan rate without any degradation of the activity. Furthermore, the calculated mass activity of the CuCo2S4 electrocatalyst is found to be 14.29 A/g and to afford a TOF value of 0.1431 s(-1) at 310 mV at a mass loading of 0.7 mg cm(-2). For comparison, nanostructures of Co3S4 and Cu0.5Co2.5S4 have been synthesized using a similar method followed for CuCo2S4. When compared to the OER activities among these three thiospinels and standard IrO2, CuCo2S4 nanosheets offered the highest OER activities at the same mass loading (0.7 mg/cm(-2)). Extensive X-ray photoelectron spectroscopy and electron paramagnetic resonance analyses for a mechanistic study reveal that introduction of Cu into the Co3S4 lattice enhances the oxygen evolution and kinetics by offering Cu2+ sites for utilitarian adsorption of OH, O, and OOH reactive species and also by offering a highly active high-spin state of octahedral Co3+ for OER catalysis.
Keywords: Bifunctional Electrocatalyst; Catalyst; Cuco2s4; Efficient Electrocatalyst; electrocatalyst; Electronic-structure; Nanoparticles; Nanosheet; oxide; oxygen evolution; performance; Recent Progress; Water oxidation; Water Splitting Hydrogen Evolution

Efficient organic photovoltaics with improved charge extraction and high short-circuit current - Mohan, Minu; Nandal, Vikas; Paramadam, Sanish; Reddy, Kasala Prabhakar; Ramkumar, Sekar; Agarwal, Sumanshu; Gopinath, Chinnakonda S.; Nair, Pradeep R.; Namboothiry, Manoj A. G. (Journal of Physical Chemistry C, 2017)
Exciton generation, dissociation, free carrier transport, and charge extraction play an important role in the short-circuit current (J(sc)) and power conversion efficiency of an organic bulk heterojunction (BHJ) solar cell (SC). Here we study the impact of band offset at the interfacial layer and the morphology of active layer on the extraction of free carriers. The effects are evaluated on an inverted BHJ SC using zinc oxide (ZnO) as a buffer layer, prepared via two different methods: ZnO nanoparticle dispersed in mixed solvents (ZnO A) and sol-gel method (ZnO B). The device with ZnO A buffer layer improves the charge extraction and J(sc),. The improvement is due to the better band offset and morphology of the blend near the ZnO A/active layer interface. Further, the numerical analysis of current-voltage characteristics illustrates that the morphology at the ZnO A/active layer interface has a more dominant role in improving the performance of the organic photovoltaic than the band offset.

Metallic cobalt to spinel Co3O4-electronic structure evolution by near-ambient pressure photoelectron spectroscopy - Reddy, Kasala Prabhakar; Jain, Ruchi; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
In the present study, valence band (VB) and core level photoelectron spectroscopy was carried out to investigate the electronic structural changes from polycrystalline Co to spinel Co3O4, via CoO at near ambient pressures (NAP; similar to 0.1). O-2 Co and H-2-CoOx gas solid oxidative and reductive interactions, respectively, have been explored with UV photons (He I) or low kinetic energy electrons (<= 16 eV) under NAP conditions. Typical VB features of Co metal, CoOx Co3O4, and a mixed phase between any two adjacent features were observed and well corroborated with core level changes. Very significant and characteristic changes were observed with Co 3d features in the VB for each stage from Co oxidation to Co3O4 as well as Co3O4 reduction to CoOx Co(3O)4 and CoO can be reversibly obtained by alternating the conditions between 0.1 mbar of H-2 at 650 K and 0.1 mbar of O 2 at 400 K, respectively. A meaningful correlation is observed between the changes in work function with cation oxidation state; small changes in the stoichiometry can strongly influence the shift in Fermi level and changes in work function under NAP conditions. Reversible work function changes are observed at a constant BE (similar to 5 ev) between oxidation and reduction conditions. While the O 2 p derived feature for CoOx was observed at throughout the redox conditions, the Co 3d band and molecular oxygen or hydrogen vibration feature shifts significantly underscoring the physicochemical changes, such as charge transfer energy and hence changes in satellite intensity. The peak close to E-F originated from the 3d(6)L final state of the octahedral Co3+ 3d band of Co3O4.

Water mediated deactivation of Co3O4 naonrods catalyst for CO oxidation and resumption of activity at and above 373 K: electronic structural aspects by NAPPES - Jain, Ruchi; Reddy, Kasala Prabhakar; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
The catalytic activity of the Co3O4 nanorods (NRs) for the CO oxidation reaction and the effect of water on the catalytic reaction have been explored with near-ambient pressure photoelectron spectroscopy (NAPPES) and mass spectral analysis. Comparative NAPPES studies have been employed to understand the elucidation of the catalytic reaction pathway and the evolution of various surface species. The results confirm the suppression of the CO oxidation activity on the Co3O4 NRs in the presence of water vapor. Various type of surface species, such as CO(ads), hydroxyl, carbonate, formate, are found to be present on the catalyst surface depending on the reaction conditions. Vibrational features of CO, O-2, and CO, were observed and shift in binding energy of these features under the reaction conditions directly suggests a change in work function of the catalyst surface. Under dry conditions, CO couples with labile 0 atoms to form CO2; however, under wet conditions, CO predominantly interacts with surface OH groups resulting in the formation of carbonate and formate intermediates. In situ studies of oxidation of CO on Co3O4 shows that CO oxidation depends not only on surface Co3+ concentration but also influenced by Co-3/Co' ratio on the catalyst surface. The carbonate was found to be a reaction inhibitor at room temperature; however, it acts as an active intermediate at 375 K and above. Above the boiling point of water, Co3O4 NR surfaces begin to show the oxidation activity even in the presence of water vapor. The intrinsic role of intermediate species was used to derive a possible reaction mechanism under different reaction conditions.
Keywords: Ambinent-temprature; carbon monoxide; Gas Shift; H Activation; In-situ; Low-temprature oxidation; Molecular-beam; Performance enhancement; Ray Photoelectron-Spectroscopyu; Thin-films

Mapping valence band and interface electronic structure changes during the oxidation of Mo to MoO3 via MoO2 and MoO3 reduction to MoO2: A NAPPES study - Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Tuning the surface energetics, especially work function (phi) of the materials, is of a great deal of interest for a wide range of surface- and interface-based devices and applications. How the phi of a solid surface changes under the reaction conditions is of paramount interest to the chemists, particularly in the areas of surface dependent phenomena such as, catalysis and electrochemistry. In the present study, by using the valence band and core-level photoelectron spectroscopy, surface-electronic changes from Mo to MoO3 via MoO2 was studied under relevant near-ambient pressure (NAP) and high temperature conditions. A very significant change in phi from Mo to MoO3 was observed and it is well corroborated with the changes in gas-phase vibrational features of O-2 in both near-ambient pressure ultraviolet photoelectron spectra (NAPUPS) as well in NAP X-ray photoelectron spectroscopy. Reversible changes in the electronic structure is observed when MoO3 was reduced in H-2 to MoO2. On the basis of the extent of oxidation/reduction of MoOx NAPUPS has shown, one or two additional peaks in the band gap at 0.6 and 1.6 eV below the Fermi level. Mo5+ features are identified in the VB and in the Mo 3d core levels with distinct features. Mo5+ features are also stable and essential to bridge MoO2 and MoO3 layers, and their co-existence. In addition, characteristic changes in Mo 4d and O 2p features observed from Mo to MoO3 and well corelated to the band gap of MoO3. Oxidation and reduction propagate from the surface to bulk; indeed, this has significant implications in surface-dependent phenomena. The present study demonstrates (a) the uniqueness of NAPUPS in identifying the subtle to large changes in the electronic structure on solid surfaces under common oxidation and reduction (in general, under reaction) conditions, and (b) relevance of NAPUPS to all surface dependent phenomena, such as catalysis and electrochemistry.

Silicon oxidation by NAPPES: From dangling bonds to oxygen islands to 2D SiOx layer to the onset of bulk SiO2 formation - Ghosalya, Manoj Kumar; Jain, Ruchi; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
Valence band and core level photoelectron spectral measurements at near-ambient pressures (NAP; up to 0.5 mbar) were made in the presence of molecular oxygen to explore the various oxidation stages of silicon surfaces. Dangling bonds feature observed on clean Si-surfaces in the valence band at ultrahigh vacuum decreases dramatically due to oxygen adsorption between ambient temperature and up to 400 K at 0.1 mbar of O-2 pressure. The adsorption of oxygen on dangling bonds appears to be localized as islands; this reflects in the surface heterogeneous character and also responsible for the broadening in the oxygen gas phase vibrational features. This is further supported by an increase in the work function and can be correlated to the presence of Hofer (molecular) precursor. When the temperature was increased to 500 K, molecular precursor species dissociates to form Si-=-0 species. This is fully supported by the change in the Si work function as well as from the observation of oxidized Si species from Si 2p core level spectra. At >= 600 K, the Si-=-0 species dissociates to form a uniform 2D oxide layer on the silicon surface, which is characterized by the reappearance of sharp vibration features for gas-phase O-2 molecules. This layer is also quite stable up to 800 K and without any further oxidation in the bulk. On increasing the temperature to 850 K at 0.2 mbar oxygen pressure, bulk Si oxidation begins and the work function increases drastically by 1 eV. An angle-dependent Si 2p spectra recorded map out the presence of elemental Si to Si4+ from bulk to the surface, respectively. A simple model is proposed to show the various stage of silicon oxidation. A continuous change in the work function and electronic states observed due to gas-lattice (O-2-Si) interaction indicates the implications for surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, 2D layered materials.

Subtle interaction between Ag and O 2 : a near ambient pressure UV photoelectron spectroscopy (NAP-UPS) investigations - Ghosalya, Manoj Kumar (Journal of Chemical Sciences, 2018)
The Ag-O2 interaction, which is at the center-stage of Ag-catalyzed partial oxidation reactions, is studied with NAP-UPS up to 0.2 mbar O2 pressure between 295 and 550 K. Three temperature regimes were identified for distinct Ag-O2 interaction, which are (a) 295–390 K, where mainly dissociative chemisorption of O2 happens, (b) 390–450 K, where diffusion of O-atoms into the sub-surfaces of Ag is prominent, and (c) >450 K, where metastable oxide forms on polycrystalline Ag surfaces. The work function (WF) of Ag changed from 4.95 (≤390 K) to 5.30 eV (390–450 K), and then to 5.7 eV (≥450 K) at 0.1 mbar O2 pressure. Oxygen population in the sub-surfaces imparts crucial modifications to Ag at 390–450 K; it makes the surface to be electron-deficient that relates to the change in the WF of Ag and facilitates the formation of space charge layer on Ag surface. Oxygen adsorbed on such modified Ag-surfaces is electrophilic in nature, and this appears at a higher binding energy in core level XPS than the chemisorbed oxygen on metallic Ag. This is supported by angle-dependent NAP-XPS studies. The subsurface population of oxygen in Ag no longer persists at >410 K when the O2 supply is removed. A high ratio of antibonding/bonding O 2p bands suggests the unique silver-oxygen interaction under the measurement conditions.
Keywords: Electronic Structure; epoxidation; heterogeneous catalysis; Surface Science

Molybdenum carbide catalyst for the reduction of CO2 to CO: surface science aspects by NAPPES and catalysis studies - Reddy, Kasala Prabhakar; Dama, Srikanth; Mhamane, Nitin B.; Ghosalya, Manoj K.; Raja, Thirumalaiswamy; Satyanarayana, Chilukuri V.; Gopinath, Chinnakonda S. (Dalton Transactions, 2019)
Carbon dioxide is a greenhouse gas, and needs to be converted into one of the useful feedstocks, such as carbon monoxide and methanol. We demonstrate the reduction of CO2 with H-2 as a reducing agent, via a reverse water gas shift (RWGS) reaction, by using a potential and low cost Mo2C catalyst. Mo2C was evaluated for CO2 hydrogenation at ambient pressure as a function of temperature, and CO2 : H-2 ratio at a gas hourly space velocity (GHSV) of 20 000 h(-1). It is demonstrated that the Mo2C catalyst with 1 : 3 ratio of CO2 : H-2 is highly active (58% CO2 conversion) and selective (62%) towards CO at 723 K at ambient pressure. Both properties (basicity and redox properties) and high catalytic activity observed with Mo2C around 700 K correlate well and indicate a strong synergy among them towards CO2 activation. X-ray diffraction and Raman analysis show that the Mo2C catalyst remains in the beta-Mo2C form before and after the reaction. The mechanistic aspects of the RWGS reaction were determined by near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) with in situ generated Mo2C from carburization of Mo-metal foil. NAPXPS measurements were carried out at near ambient pressure (0.1 mbar) and various temperatures. Throughout the reaction, no significant changes in the Mo2+ oxidation state (of Mo2C) were observed indicating that the catalyst is highly stable; C and O 1s spectral results indicate the oxycarbide species as an active intermediate for RWGS. A good correlation is observed between catalytic activity from atmospheric pressure reactors and the electronic structure details derived from NAPXPS results, which establishes the structure-activity correlation.

Promising visible-light driven hydrogen production from water on a highly efficient CuCo2S4 nanosheet photocatalyst - Chauhan, Meenakshi; Soni, Kiran; Karthik, P. E.; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S.; Deka, Sasanka (Journal of Materials Chemistry A, 2019)
Here we report the development of CuCo2S4 nanosheets (NSs) as a promising semiconductor photocatalyst for the first time for water splitting reactions under visible light ( 420 nm) conditions, without the support of any noble metal co-catalyst. These NSs were produced via a simple hydrothermal route and have desirable properties with a band gap of 2.24 eV, and are photo-catalytically active under visible light with an apparent quantum yield (AQY) of 2.48%. Under visible light, CuCo2S4 NSs exhibit excellent weight-normalized photoactivity that generates approximate to 25900 mol h(-1) H-2 for 1 g of material with sulphide + sulphite as the sacrificial agent under 7.68 mW cm(-2) illumination, which is the best evolution reported for any chalcogenide semiconductor material without any co-catalyst to date with unprecedented long-term operational stability (up to 12 h study time). The rate and number of hydrogen gas molecules produced are 8.2855 x 10(15) s(-1) cm(-2) which remained constant for three catalytic cycles with a turnover frequency (TOF) value of 0.017 s(-1). The effect of Cu substitution on photoactivity was also investigated for comparative studies and it was found that CuCo2S4 NSs show superior activity to Cu0.5Co2.5S4 and Co3S4. These CuCo2S4 NSs absorb the entire visible range of the spectrum from 420 to 800 nm, and have a highly populated density of states at the Fermi level and a high donor concentration of 7.22 x 10(18) cm(-3) which have been evaluated by Mott-Schottky analysis and favourable adsorption of H+ on S-sites and conversion to H-2 corroborate their efficient photocatalytic activity.

Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen

Gas-solid interactions with reactive and inert gas molecules by NAPUPS: can work function be a better descriptor of chemical reactivity? - Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Mhamane, Nitin B.; Ranjan, Ravi; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2020)
The gas-phase vibrational spectra of reactive (H(2)and O-2) and inert gases (N(2)and Ar) have been studied by near-ambient pressure (NAP) ultraviolet photoelectron spectroscopy (NAPUPS) up to 0.3 mbar pressure. The results obtained are divided into two parts and discussed. In the first part, the photoelectron spectra of monoatomic Ar and some homonuclear diatomic molecules, such as H-2, O-2, and N-2, have been recorded by NAPUPS and the effect of pressure on their energy position has been studied. It has been demonstrated that NAPUPS could be an essential tool to determine the intermolecular or interatomic interactions. In the second part, we have evaluated the influence of different solid surfaces on the binding energy (BE) position, the pattern of the vibrational features of diatomic N(2)molecules, and the first atomic levels (3p(3/2)and 3p(1/2)) of monoatomic Ar. It has been observed that with a change in the (electronic/chemical) nature of the surface, the BE of the above features also changes and reflects the change in the work function (phi) of the material. It is to be noted that Ar is an inert/noble gas and N(2)is the most stable molecule, and the above changes observed underscore that they can be employed as probe atoms/molecules to explore even the minor changes that occur on a solid surface due to a variety of reasons. Further, if the solid surface undergoes any chemical/electronic changes due to gas-solid interaction, such as oxidation/reduction, the phi of the surface changes again; this highlights the precise identification of the changes that occur under the reaction/measurement conditions. Therefore, the change in the BE of the gas-phase features can be used to determine even the minor changes in the phi of solid surfaces during the reaction or due to the reaction. The present findings have implications in probing the surface changes that occur in any surface-dependent phenomena, such as heterogeneous catalysis, electrochemistry, and materials that are predominantly controlled by surface contribution, such as layered (2D) materials, nanomaterials.

Rationally designed, efficient, and earth-abundant Ni-Fe cocatalysts for solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Reddy, Kasala Prabhakar; Saikia, Pranjal; Gopinath, Chinnakonda S. (ACS Sustainable Chemistry & Engineering, 2021)
Developing highly efficient and affordable catalysts for solar hydrogen (H-2) generation is crucial, and employing a cocatalyst from earth-abundant elements has a critical role to play. In this context, different compositions of earth-abundant Ni-Fe alloy (1:1, 1:3, and 3:1) have been prepared by hydrothermal method; subsequently, 1 wt % of these Ni-Fe cocatalysts were integrated with TiO2-P25 and thoroughly characterized. The resultant catalysts have been evaluated for solar H-2 production, in powder and thin film forms, under one sun condition and in direct sunlight. Interestingly, all the catalysts in the thin film form exhibit superior hydrogen yield (HY), up to 27 times higher activity than its powder counterpart. Among the photocatalysts, Ni-Fe/TiO2 (3:1 = Ni/Fe; NFT31) composition exhibits the best HY in thin film (8.27 mmol.h(-1).g(-1)) and exceeds all other compositions of catalyst. It is also to be reported that HY measured for the powder form with 1 mg shows 3-17 times higher activity than that measured with 25 mg. This is mainly attributed to effective solar light absorption with a smaller amount of photocatalyst either spread over large area in a thin film form or well-dispersed in suspension forms. Furthermore, the enhanced activity obtained with Ni-Fe/TiO2 photocatalysts is also ascribed to strong electronic integration of Ni-Fe cocatalyst with TiO2 and higher performance obtained with a thin film is attributed to increased charge carrier generation and subsequent charge separation and effective utilization. A decrease in work function of TiO2 by 0.6 eV was observed after its integration with cocatalyst in NFT31.
Keywords: Cocatalyst; Hydrogen; Ni-Fe alloy; solar energy; TiO2; water splitting